A 3D inlet distributor employing copper foam for liquid replenishment and heat transfer enhancement in microchannel heat sinks. (August 2020) - Hong, Sihui; Dang, Chaobin; Hihara, Eiji
Highlights: A 3D inlet distributor employing copper foam was proposed to facilitate continuous liquid wetting. A physical heat transfer model for microchannel employing copper foam was established. Heat transfer enhancement of the 3D inlet distributor was verified with flow boiling tests. Effect of operating condition, orientation and thickness of copper foam were comparatively investigated. Valid self-sustained liquid supply and heat transfer improved for an actual-sized heat sink was realized. Abstract: The application of two-phase flow boiling to microchannel heat sinks has attracted increasing attention owing to the compact design and high efficiency of dissipating heat. However, undesirable heat transfer deterioration and premature critical heat flux are commonly encountered in real-life applications of two-phase flow cooling devices. One significant challenge in utilizing two-phase flow boiling in microchannels lies in preventing the thin liquid film and in-time liquid replenishment from being interrupted by the rapid bubble elongation and chaotic vapor-liquid interface in the channel. In the present work, a 3D inlet distributor employing copper foam is proposed as an extra liquid feeding path to facilitate continuous liquid wetting of the boiling surface and improve the heat transfer performance. A physical heat transfer model accounting for the differences in microchannel void fraction and liquid film thickness caused by the copper foam layer (CFL) has been proposed to describe the working mechanism. The validity of the proposed 3D inlet distributor in heat transfer enhancement was verified using a series of flow boiling tests, employing deionized water as the working fluid. It was found that the local overheating of the microchannel heat sink was demonstrably reduced for all the heat flux values ( q ) in the tests after adopting the CFL, with a maximum reduction of 14 K at q = 397.6 kW/m 2, where local dry-out was successfully inhibited. The heat transfer coefficient of the microchannel heat sink with the CFL was improved by approximately 1.7 times compared to the case without the CFL and could be maintained at 41 kW/m 2 K during elongated bubble flow and annular flow patterns. In addition, the proposed distributor was capable to resist gravity and long-term severe boiling, thus achieving superior and reliable performance under various orientations as well as during long operating hours.